A Comprehensive Insight into the Phytochemical, Pharmacological Potential, and Traditional Medicinal Uses of Albizia lebbeck (L.) Benth. (21st April 2022) - Balkrishna, Acharya; Sakshi; Chauhan, Mayur; Dabas, Anurag; Arya, Vedpriya
Abstract : Background . Albizia lebbeck is a deciduous tree having tremendous medicinal utilities, for example, respiratory, skin, gastrointestinal, oral disorders, eye, urinary, genital, anorectal, inflammatory, and neurological disorders, and venereal diseases. Several studies have been undertaken on the medicinal and traditional values of A. lebbeck . Objective . The detailed information about its medicinal uses and pharmacological implications is highly scattered and distributed in different data sources. Hence, the study was conducted to supply an inclusive review of its ethnomedicinal uses, phytochemicals, and the available pharmacological attributes supporting its efficiency in traditional medicine. Method . Literature surveys were conducted on this medicinal plant via search engines like Google Scholar, PubMed, and Science Direct, and obtained information up to December 2020 has been assessed and analyzed for this study. Results . Systematic investigation revealed that A. lebbeck consists of various phytochemicals, including major alkaloids, flavonoids, saponins, and terpenoids. Its crude extract, fraction, and bioactive compounds exhibited potent adulticidal, antiallergic, anticancer, anticonvulsant, antidiabetic, antidiarrheal, anti-inflammatory, antimicrobial, antinociceptive, antioxidant, antiparasitic, antipyretic, antivenom, estrogenic, neuroprotective, nootropic, ovicidal, and wound healing activities. Conclusions . This study proposes that A. lebbeck remains a rich source of phytochemicals with various biological activities which possess outstanding therapeutic benefits to humanity across the world. However, studies are required to estimate the potential side effects. Moreover, mechanistic physiognomies of the isolated compounds with known bioactivities are quite limited; thus, forthcoming research needs to focus on the mechanisms of these active phytochemicals to facilitate their potential enrolling for drug discovery.